2005
DOI: 10.1086/444548
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Polymerase W748S Mutation: A Common Cause of Autosomal Recessive Ataxia with Ancient European Origin

Abstract: Mutations in the catalytic subunit of the mitochondrial DNA polymerase gamma (POLG) have been found to be an important cause of neurological disease. Recently, we and collaborators reported a new neurodegenerative disorder with autosomal recessive ataxia in four patients homozygous for two amino acid changes in POLG: W748S in cis with E1143G. Here, we studied the frequency of this allele and found it to be among the most common genetic causes of inherited ataxia in Finland. We identified 27 patients with mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
285
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 281 publications
(297 citation statements)
references
References 28 publications
9
285
0
3
Order By: Relevance
“…We analyzed the POLG genomic region haplotypes of 17 unrelated patients from Australia or New Zealand (14 from Australia and three from New Zealand), who all carried at least one W748S þ E1143G or A467T allele, as our previously published European samples. 12 The corresponding nucleotide changes are the following (GenBank NM_002693; sequence numbering starts from ATG): c.2243G4C (p.W748S), c.3428A4G (p.E1143G), and c.1399G4A (p.A467T). The other mutations, including the chromosomes carrying the G848S mutation (c.2542G4A), are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We analyzed the POLG genomic region haplotypes of 17 unrelated patients from Australia or New Zealand (14 from Australia and three from New Zealand), who all carried at least one W748S þ E1143G or A467T allele, as our previously published European samples. 12 The corresponding nucleotide changes are the following (GenBank NM_002693; sequence numbering starts from ATG): c.2243G4C (p.W748S), c.3428A4G (p.E1143G), and c.1399G4A (p.A467T). The other mutations, including the chromosomes carrying the G848S mutation (c.2542G4A), are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…3 -9 We and collaborators have previously reported the W748S mutation as a common cause of ataxia with ancient European origin. 12 The carrier frequency of the W748S mutation was 1:125 in Finland, and the combined frequency of W748S and A467T mutations in the Norwegian population was estimated to be as high as 1:50, 12,14 making it the most common pathogenic POLG mutation. We studied the European W748S disease chromosomes in Finnish, British, Belgian, and Norwegian patients and showed that they all originate from a single common ancient founder.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…POLG1 was downregulated in patients ( Figure 1). POLG1 is one of the causative genes for mitochondrial diseases, such as chronic progressive ophthalmoplegia 35 and mitochondrial recessive ataxia syndrome, 36 both of which frequently comorbid with mood disorders. We showed that transgenic mice with neuron-specific expression of mutant Polg1 displayed BD-like phenotypes.…”
Section: Biomarkers Of Bipolar Disorder T Kato Et Almentioning
confidence: 99%